Pulse-like near-fault ground motion effects on controlled rocking steel cores. (June 2021) - Mohajeri, Arian; Rahgozar, Navid; Moghadam, Abdolreza S.
Abstract: Controlled rocking steel cores (CRSCs) with reliable self-centering capability have been known as a low-damage seismic force-resisting system. The flag-shaped hysteresis response of CRSCs can be provided using unbonded post-tensioning tendons and replaceable energy dissipation devices. This paper examines the seismic performance of CRSCs subjected to a suite of pulse-like near-field and far-field ground motions. Non-linear dynamic response analysis is performed for 3-, 6-, 9-, and 12-story archetypes with single and coupled configurations. Results are quantified for different seismic responses, and the influences of earthquake type and structural configuration are compared from various aspects. The findings indicate remarkable changes in the performance of CRSCs due to modeling and ground motion properties. The outcomes reveal that rocking-core archetypes are efficient for mitigating residual damage and restricting peak displacements under both far- and near-field motions.